Komparasi Multi Criteria Decision Making Method Penerimaan Bantuan Siswa Miskin - Nungsiyati Nungsiyati; Didi Susianto; Noca Yolanda Sari; Siti Mukodimah (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2023)
Poor Student Assistance (BSM) is government assistance in the form of a sum of cash that is given directly to students who come from poor families. BSM recipients are students who have been determined by the Ministry of Education and Culture (Kemdikbud) based on a predetermined mechanism. Assistance provided by the government to students from underprivileged families is not transparent so some BSM are not on target. In an effort to minimize target inaccuracies, a study was made with Multi Criteria Decision Making (MCDM) which is a decision-making method for determining the best alternative out of a number of alternatives based on certain criteria. The ranking of beneficiaries is determined using a comparison of the Simple Additive Weighting Method and the Weighted Product Method, which are the MCDM model. Manual testing was carried out on 5 (five). From the test results of the Simple Additive Weighting Method, Alternative 4 obtained the highest score. While the results of the Weighted Product method test show the highest results in Alternative 3. The difference in the calculation results of the two methods used is influenced by several factors such as the performance rating value of each alternative, the weight of the criteria, and mathematical calculations for each method, and because the criteria used do not have different weights so that the calculation results become less significant.